2018
DOI: 10.1063/1.5060628
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic study of slowing-down α particles transport due to trapped electron mode turbulence

Abstract: Transport of α particles due to trapped electron mode (TEM) turbulence is investigated from nonlinear and quasilinear gyrokinetic simulations. We consider both slowing-down and Maxwellian distribution functions for α particles, and identify and compare diffusive and convective parts of α particle transport as a function of the α particle's energy normalized to the background plasma temperature. We find that TEM induces much lower transport of energetic α particles such as fusion products than that of thermal H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 37 publications
3
26
1
Order By: Relevance
“…It can be seen that the diffusivity of α particles is much smaller than that of helium ash due to the factor of ρ H /ρ α , which will be shown quantitatively later. This relationship is consistent with the results from gyrokinetic simulation [33], thus the density profile of α particles can be significantly peaked as already pointed out in [2].…”
Section: Normalized Transport Coefficients Of Helium Ash In D-t Plasm...supporting
confidence: 92%
See 3 more Smart Citations
“…It can be seen that the diffusivity of α particles is much smaller than that of helium ash due to the factor of ρ H /ρ α , which will be shown quantitatively later. This relationship is consistent with the results from gyrokinetic simulation [33], thus the density profile of α particles can be significantly peaked as already pointed out in [2].…”
Section: Normalized Transport Coefficients Of Helium Ash In D-t Plasm...supporting
confidence: 92%
“…where ρ H = v thH /Ω H . It can be seen from equations ( 32) and (33), α particles could influence the transport of helium ash via affecting the real frequency and growth rate, and the magnitude of normalized diffusivity as well as convective velocity is related to FLR effects.…”
Section: Rv Hementioning
confidence: 99%
See 2 more Smart Citations
“…This work is also limited to simulations with electrons, deuterium and tritium fuels, and helium ash, excluding energetic alpha particle dynamics. It has been reported that TEM drives low-level transport of alpha particles 39 . The resonant interactions between energetic particles and micro-instability will be significant for ITG modes 40 , 41 but not for TEM and ETG modes because the propagation directions are opposite 42 .…”
Section: Discussionmentioning
confidence: 99%